Deindustrialization in Colombia - Zamudio, Luis Eudoro Vallejo (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The participation of the Colombian industry in GDPwas highest in 1975,when it reached 23.2 %, later, in the eighties dropped to 21.3 % on average, but from the nineties, was down sharply to stand at 15.1 %. Today it represents 11.2 %, i.e., 12 percentage points below the year of the highest participation.